Studi Rancangan Unit dan Instalasi Pengolahan Air Limbah Tambak Udang Di Desa Kertasada Kecamatan Kalianget Kabupaten Sumenep - Desmantri R, Ach.; Sulfa, Diana (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2024)
Shrimp ponds located in Kertasada Village, Kalianget District have a total of 8 shrimp ponds. With a total area of 4,532 m2. The problem that exists in this shrimp pond is that there is no treatment of shrimp pond wastewater before it is returned to the waters. This study aims to determine the design of shrimp pondwastewater management units installations in Kertasada Village, Kalianget District. The type of research used is descriptive quantitative research with object of research units installation of wastewater treatment with biofilter system aerobic anaerobic. The results of this study obtained that the discharge of shrimp pond waste as much as 498,52 m3 / day from a pond area of 4,532 m2 of liquid waste from the production process is directly channeled to the wastewater receiving body, namely rivers with BOD5, TSS, and NH3 content of 9,727 Mg / l , 2,33 Mg / l, 0,007 Mg / l.